Mandibular resection via mandibular-lip L flap for the treatment of extensive multicystic Ameloblastoma - Edson Martins Oliveira Junior; Pedro Dantas Segundo; Luciano Macedo Santos Silva; Jorge Antonio Ferreira Marques (University of São Paulo, 2013)
Ameloblastoma is a benign odontogenic tumor accounting for 1% of all tumors of the maxilla and mandibula. The mandibula is committed in 85% of the cases. The tumor is locally invasive, able to infiltrate bone marrow spaces, without radiographic or macroscopic evidence. High recurrence rates are associated with different surgical techniques, which range from simple tumoral enucleation to extensive resections. The authors report a case of a 26-year old female patient with an 8-year history of progressive, non-tender, swelling of the left mandibular region. The intraoral examination showed that the floor of mouth was raised on the left side by a bulging along the bottom of the left mandibular vestibule as well as the lingual region. Over this area, there were ulcerated areas in the alveolar region of the molars and mucosal fenestration in the alveolar and lingual regions were present. A panoramic radiography revealed a multicystic lesion, resembling the soap-bubble shape endosseous lesion. The computed tomography revealed an expandable multicystic lesion compromising both mandibular cortices. The patient underwent a biopsy, which revealed the diagnosis of a multicystic variant of Ameloblastoma, with plexiform pattern, treated with left mandibular resection and immediate installation of a customized prosthesis. After a year of follow-up, no evidence of the tumor relapse was evidenced.